The Pengembangan Perangkat Pembelajaran Materi Bangun Ruang Sisi Lengkung Berbasis Etnomatematika Berbantuan Aplikasi Google Form sebagai Penunjang Pembelajaran Daring - Zahro, Sofhia Ma'rifatuz; Sunardi, Sunardi; Suwito, Abi; Susanto, Susanto; Safrida, Lela Nur (Kadikma, 2021)
This research aims to know the process and the result of the development of Mathematics Learning Instruments for ethnomathematics based curved space chapter with the help of the Google Form aplication as a support for online learning. This research is development research. Learning instruments development model refers to four D models. The product of this research are teaching materials, student’s worksheet, and evaluation test. This research took place at IX A of junior high school 2 Puger, Jember with consist 36 students. The data collection methods used in this research are the interview, test, and questionnaire. Based on data analysis, this research has three result. First, the learning instrument developed have valid criteria. Secondly, the learning instrument developed have practical criteria based on interview and student’s responses. Third, the learning instrument developed have effective criteria based on student’s score and student’s positive responses.